Discovering Girard - Kirwan, Michael (Cowley Publications, 2005)
"Really wonderful; an elegantly written initiation into the mimetic theory. I am lucky to have interpreters who understand what I want to say and who can write so well."- The work of Rene Girard is hugely influential in literature and cultural studies. But it is in understanding the relationship between religion and violence that his theory has created its greatest impact. Girard's understanding of mimetic rivalry and conflict and of scapegoating is seen by many to be the key to a completely new understanding of Christianity. Girard's name evokes curiosity and-often-strong feelings among devotees and skeptics. Discovering Girard is the first book to present Girard's work to a wider audience. It explains and appraises Girard's mimetic theory, shows its impact on theology and other disciplines, and manages to convey the excitement that a discovery of Girard's ideas often generates in readers."